The Protective Effect of Dexmedetomidine Against Ischemia-Reperfusion Injury after Hepatectomy: A Meta-Analysis of Randomized Controlled Trials - Huang, Ya-Qun; Wen, Rui-Ting; Li, Xiao-Tong; Zhang, Jiao; Yu, Zhi-Ying; Feng, Yu-Fei (Frontiers in Pharmacology, 2021)
Background: Hepatic inflow occlusion proceeded to reduce blood loss during hepatectomy induces ischemia-reperfusion (IR) injury in the remnant liver. Dexmedetomidine, a selective α2-adrenoreceptor agonist used as an anesthetic adjuvant, has been shown to attenuate IR injury in preclinical and clinical studies. However, a meta-analysis is needed to systematically evaluate the protective effect of perioperative dexmedetomidine use on IR injury induced by hepatectomy. Methods: A prospectively registered meta-analysis following Cochrane and PRISMA guidelines concerning perioperative dexmedetomidine use on IR injury after hepatectomy was performed via searching Cochrane Library, PubMed, EMBASE, ClinicalTrials.gov, Web of Science, CNKI, WanFang, and Sinomed for eligible randomized controlled trials up to 2021.3.31. The main outcome is postoperative liver function. Risk of bias was assessed by the Cochrane Risk of Bias tool. Review Manager 5.3, and Stata12.0 were applied to perform data analyses. Results: Eight RCTs enrolling 468 participants were included. Compared with 0.9% sodium chloride, dexmedetomidine decreased serum concentration of ALT (WMD = -66.54, 95% CI: -92.10 to -40.98), AST (WMD= -82.96, 95% CI: -106.74 to -59.17), TBIL (WMD = -4.51, 95% CI: -7.32 to -1.71), MDA (WMD = -3.09, 95% CI: -5.17 to -1.01), TNF-α (WMD = -36.54, 95% CI: -61.33 to -11.95) and IL-6 (WMD = -165.05, 95% CI: -225.76 to -104.34), increased SOD activity (WMD = 24.70, 95% CI: 18.09 to 31.30) within postoperative one day. There was no significant difference in intraoperative and postoperative recovery parameters between groups. Conclusions: Perioperative administration of dexmedetomidine can exert a protective effect on liver IR injury after hepatectomy. Additional studies are needed to further evaluate postoperative recovery outcomes of dexmedetomidine with different dosing regimen.